Analisis Beak Even Point dan Perancangan Alat Bantu Pencatatan Penjualan dan Barang Kembali Menggunakan Template Excel di Toko Korea Silver - Salim; Agus Tri Santosa; Nisa Nur Apipah (LPPM Sekolah Tinggi Teknologi Cipasung, 2022)
Korea Silver Store was established on March 09, 2017, located at Panyingkiran number 55 Singaparna, is a business engaged in the sale and purchase of silver jewelry. The Korea Silver shop still records daily data manually, namely writing in the cash book tends to be ineffective, so the owner has not been able to analyze the minimum sales volume of silver so that the business carried out does not suffer losses. The research method used to calculate the volume of silver sales using break-even analysis and the method of recording daily data using an excel template. The results of the excel template design show that sales data display, returned goods, and daily total sales and goods returns are obtained. While the results of the calculation of the break-even point obtained a silver sales volume of 16,577.5893 grams or Rp. 341,692,333.